Strategies in Improving Students’ TOEFL Scores at University of Gunung Leuser - Zaini Hasan (Jurnal Scientia, 2021)
English as an international language has been acknowledged. Nobody wants to be left behind in terms of international relations and competition. One must have English proficiency to win the match and conquer the world. To indicate competence is through TOEFL. The students of the University of Gunung Leuser have also been conducting such kinds of tests to measure their English proficiency but still in low results. Through analysis of variables using regression and SWOT, factors influencing English proficiency and the strategies used to improve their English, it is found that their competence is methods of teaching, learning media, learning materials, and instructors. Then, to increase their competence, the suggested strategies are improving the TOEFL course program, practising English continually, using English forums, watching English films, practising English conversation, reading English books, and providing the needed infrastructures to support the English learning environment.